TRANSLATION ERRORS OF FLIGHT ATTENDANT STUDENTS OF PSPP YOGYAKARTA - Heri Wira Andesta; I Wayan Dirgayasa; Eddy Setia (LINGUISTIK TERAPAN, 2018)
This research dealt with Translation Errors of Flight Attendant Students of PSPP Yogyakarta in translating flight attendant announcement. The aims of this study were (1) To investigate the kinds of error in translating flight attendant announcement made by flight attendant students, and (2) To explain the reasons of the students made the errors. The method used in this research is descriptive qualitative.The subjects are nineteenfligth attendant students of PSPP Yogyakarta. The instruments for collecting data aretranslation testand interview. The translation test was used to obtain the kinds of error, and the interview was used to obtain the reasons of flight attendant students made the errors.The data were analyzed by Miles and Hubberman and saldana’s data analysis. The result of this research showed that (1)there are five kinds of error made by flight attendant students,but they are not proportional distributed the example,semantic errors(43.69), and errors in the production of verb group (5.63). (2) there arethreecauses of error made by flight attendant students,but they are not proportional distributed the example,intralingual transfer (58.26), and translation (8.66). Keywords: Flight Attendant Student, Translation Errors